"The scientific flourishing of Emotion-Focused Therapy": a bibliometric analysis of EFT articles in Web of Science databases. (3rd July 2022) - Mónaco, Estefanía; Goldman, Rhonda N.; Montoya-Castilla, Inmaculada
ABSTRACT: Emotion-Focused Therapy (EFT) is an empirically supported humanistic treatment that considers clients' emotional processes as the path to therapeutic change. The present aim was to develop a bibliometric study of EFT articles published in the Web of Science (WoS) Core Collection. Books and chapters were not included in this research. The bibliometric analysis was performed using Hiscite and VosViewer. Results showed 273 publications on EFT in WoS, the first being in 1994. The most relevant areas were depression and anxiety. The most productive author is Greenberg (n = 56; GCS = 2050). The 51.28% of publications corresponds to the last five years (2016–2020), observing a substantial increase in publications comparing with previous years. It is concluded that EFT is a psychotherapeutic orientation in recent scientific growth, with potential interest for further development in next years. The absence of results in WoS prior to 1994 is a limitation, given the origins of EFT in the 1970s. Extension of this study is recommended, including: publications about emotionally focused therapy, publications from other databases different from WoS, together with books and chapters. The importance of these results is discussed to allow other researchers and professionals to know deeply about the scientific production in EFT and its impact.